2013
DOI: 10.1371/journal.pone.0063438
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of Preventive Treatment for Intestinal Schistosomiasis among School Children in Jinja District, Uganda: A Cross Sectional Study

Abstract: BackgroundIn Uganda, the current national health sector strategic and investment plan underscores schistosomiasis as one of the diseases targeted for elimination by the year 2015. However, uptake of treatment among school children is unknown but suspected to be low. We estimated the uptake and predictors of preventive treatment with praziquantel.MethodsIn a cross sectional study carried out in Jinja district of Uganda, a random sample of 1,010 children in 12 primary schools was questioned about their uptake of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
85
6

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(97 citation statements)
references
References 28 publications
6
85
6
Order By: Relevance
“…The uptake of praziquantel for schistosomiasis control has also been reported to be low among school children in Jinja district in Uganda, where it was estimated at 28.2% during the 2011 MDA (Muhumuza et al, 2013b). Similarly, low levels of drug uptake among school children have been reported in Kenya (Miguel & Kremer, 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The uptake of praziquantel for schistosomiasis control has also been reported to be low among school children in Jinja district in Uganda, where it was estimated at 28.2% during the 2011 MDA (Muhumuza et al, 2013b). Similarly, low levels of drug uptake among school children have been reported in Kenya (Miguel & Kremer, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…In Jinja district, Schistosoma mansoni is highly endemic in areas along Lake Victoria, with 35% of the school-age children harbouring moderate infections of 116.1 eggs per gram (epg) of stool (Muhumuza et al, 2013b). The World Health Organization (WHO) recommends regular treatment programmes for schistosomiasis to target school-age children who could be reached through the primary school system (Engels et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The majority of research in Uganda has been carried out along Lake Victoria and Lake Albert where infection rates have remained high. Local-level research has found that among people along the lakeshores there is often low drug coverage and, in some cases, there has been resistance to the distribution (Parker et al, 2008;Muhumuza et al, 2013Muhumuza et al, , 2015. Despite multiple rounds of free distribution of praziquantel, high rates of reinfection in both adults and children have persisted, even up to 80-90% at some locations (Kabatereine et al, 2011;Seto et al, 2012;Allen & Parker, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, it was possible to estimate drug uptake at many schools in Uganda. Overall, the uptake of praziquantel by children in schools was higher than the rate reported by Muhumuza et al (2013) from Jinja, although it was very variable, and still well below the WHO's 75% target. Examples are provided below.…”
Section: Is Deworming Effectively Delivered In Ugandan Schools?mentioning
confidence: 57%
“…Recently, consumption of praziquantel by children in Uganda has also been studied by another research team in the area around Jinja (Muhumuza et al, 2013). The findings have tended to confirm those presented above.…”
Section: Mass Drug Administration In East African Schools S135mentioning
confidence: 70%